The correlations between demographic factors, self-efficacy, and quality of life among Indonesian patients with ischemic stroke: A cross-sectional study - Nabila Azzahra; Fitria Handayani; Wahyu Hidayati (Belitung Nursing Journal)
Background: Ischemic stroke is the primary cause of neurological disability and can lead to psychological issues that affect self-efficacy. Changes in self-efficacy, in turn, influence the overall quality of life. Although many studies have examined factors that affect self-efficacy, quality of life, or both, few have specifically explored the role of demographic factors in shaping the quality of life in patients with ischemic stroke.